'Métis' Child Removal in French Indochina: Change and Continuity from the Second World War to Decolonisation - Antonisen, Ida Kaae (Culture and History: Student Research Papers, 2024)
In this article, the practice of removing mixed-race, or métis, children from their indigenous mothers in French Indochina is examined. While the changed circumstances of the Second World War and the ensuing process towards decolonisation forced colonial authorities to rethink their priorities, the practice of child removal remained constant. Against the backdrop of this persistent and relatively unchanging practice, changes and continuities in rhetoric about and justifications for child removal reveal underlying colonial interests and anxieties around race, memory, and maintaining French influence, even beyond the official end of French colonial rule.